Wednesday
March 29, 2017

Post a New Question

Posted by on .

i don't get this whole concept what-so-ever so lets start with problem one y= -3X +5
5 X - 4y = -3

  • sovle by substution - ,

    Your first equation tells a value for Y. Substitute that in the second equation.

    5x - 4(-3x + 5) = -3
    5x + 12x - 20 = -3
    17x = 20 - 3
    17x = 17
    x = 1

    Now substitute 1 for x in the first equation to find a value for y.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question